Glycemic Variability: An Independent Predictor of Mortality and the Impact of Age in Pediatric Intensive Care Unit - Du, Yuhui; Liu, Chengjun; Li, Jing; Dang, Hongxing; Zhou, Fang; Sun, Yuelin; Xu, Feng (Frontiers in Pediatrics, 2020)
Objective: To compare the ability of different indices of glycemic variability (GV) in the prognostic evaluation of critically ill children and investigate whether heterogeneity of glucose control exists within this population group. Methods: We conducted a retrospective study of the GV data collected from patients admitted to the pediatric intensive care unit, Children's Hospital of Chongqing Medical University between January 2016 and December 2016. We calculated the mean glucose level (MGL) and four indices of GV, namely, standard deviation (SD), coefficient of variation (CV), mean amplitude of glycemic excursion (MAGE), and glycemic lability index (GLI). The 28-day mortality was considered as the primary endpoint. Results: Survivors and non-survivors showed significant differences in terms of the SD, CV, MAGE, and GLI (P < 0.05, for all). However, GLI was superior to the other indices and showed an independent association with ICU mortality (odds ratio [OR], 1.082; 95% confidence interval [CI], 1.031–1.135; P < 0.01). Sub-group analysis disaggregated by quartiles of MGL and GV revealed that younger subjects (age ≤ 36 months) had significantly higher mortality in the lowest quartile of the MGL and in the highest quartile of GV; the older children (age > 36 months) experienced significantly higher mortality in the highest quartiles of MGL and GV. Conclusion: GV is closely associated with mortality, and among all glucose parameters evaluated, GLI was found to be the strongest predictor of outcomes. This paper is the first report of age being a potentially important modifier of the association between GV, MGL, and mortality in critically ill children.